Wernicke's Encephalopathy in Type 2 Achalasia: Case Report and Literature Review - Diana N. Rodriguez MD; Kriti Gera MD; Bishal Paudel MD; Angela Pham MD (SAGE Publishing, 2023)
Achalasia is primarily a smooth muscle motility disorder of the esophagus driven by aberrant peristalsis and failure of sphincter relaxation. Notably, achalasia is a heterogeneous disease with primarily 3 possible pattern subtypes. According to the review of current cases and literature regarding achalasia, patients primarily present with dysphagia, usually to solids and, if progressed, to solids and liquids. Rarely, untreated achalasia may result in thiamine deficiency and present as Wernicke-Korsakoff syndrome (WKS). This acute neurologic condition primarily affects the central and peripheral nervous system and is known by the triad of ataxia, ophthalmoplegia, and confusion. Individuals who present with WKS typically have a notable history of chronic alcohol abuse with decreased thiamine intake and metabolism. Although less common, individuals with WKS may have a pertinent history of starvation, anorexia nervosa, and malnutrition. This case highlights a unique presentation of Wernicke's encephalopathy (WE) in a 30-year-old woman with severe type II achalasia complicated by a 60-pound weight loss in a span of 2 months. According to our literature review, there have only been 2 previously reported cases of severe achalasia leading to the development of WE. Considering the limited number of case reports available, WE must be in the differentials in patients with underlying achalasia, and our case report highlights this unusual presentation with corresponding brain imaging and manometry testing.